Diagnostic difficulties in Hodgkin disease - Pais, Fátima; Esteves, Idália; Couceiro, António; Pina, Raquel; Ilídio, José (Portuguese Journal Internal Medicine, 1997)
The authors present a case of Hodgkin's disease. The diagnosis was made when the disease had already two years of evolution. Some coments are made about the difficulty on the diagnosis of this disease.